Understanding the intention to purchase halal cosmetic products among consumers - Noreen Noor Abd Aziz; Eta Wahab; Nurul Ashykin Abd Aziz; Nurul Aien Abd. Aziz (2014)
Abstract: Malaysia is being targeted by manufacturers not only as one of the fastest economic growth but also it comprises of 65 percent of Muslim adherents or around 19 million of Muslims. There is a current trend in the global industry of cosmetics upon the existence of Halal cosmetics products. Most of the users are conscious of the ingredients in the manufacturing of cosmetic products. As the market grows rapidly, cosmetics manufactures have eagerness to dominate the market and come out with a variety of products in order to pursue and satisfy customer simultaneously. Thus, the objective of this paper is to propose a new conceptual framework for halal cosmetics products. This paper identifies the antecedent factors that influence the intention to purchase halal cosmetics products among consumers. Knowledge, purity and safety have also been found to influence the customers to buy halal cosmetics products. The findings indicate that there is relationship between independent variables (attitude, subjective norm, perceived behavioral control, knowledge, purity and safety) and dependent variable i.e, intention. Safety has been identified as the main factor that influences the intention to purchase halal cosmetics products.